Comb-like dextran copolymers: A versatile strategy to coat highly porous MOF nanoparticles with a PEG shell. (1st November 2019) - Cutrone, Giovanna; Qiu, Jingwen; Menendez-Miranda, Mario; Casas-Solvas, Juan M.; Aykaç, Ahmet; Li, Xue; Foulkes, Daniel; Moreira-Alvarez, Borja; Encinar, Jorge R.; Ladavière, Catherine; Desmaële, Didier; Vargas-Berenguel, Antonio; et al.
Graphical abstract: Highlights: A family of carbohydrate comb-like copolymers was synthesized. Copolymers enabled effective nanoMOF surface functionalization. Alendronate moieties ensured a firm anchoring to nanoMOFs surface. The non-covalent coating procedure was fast and devoid of organic solvents. PEG chains dramatically reduced the recognition and uptake by macrophages. Abstract: Nanoparticles made of metal-organic frameworks (nanoMOFs) are becoming of increasing interest as drug carriers. However, engineered coatings such as poly(ethylene glycol) (PEG) based ones are required to prevent nanoMOFs recognition and clearance by the innate immune system, a prerequisite for biomedical applications. This still presents an important challenge due to the highly porous structure and degradability of nanoMOFs. We provide here a proof of concept that the surface of iron-based nanoMOFs can be functionalized in a rapid, organic solvent-free and non-covalent manner using a novel family of comb-like copolymers made of dextran (DEX) grafted with both PEG and alendronate (ALN) moieties, which are iron complexing groups to anchor to the nanoMOFs surface. We describe the synthesis of DEX-ALN-PEG copolymers by click chemistry, with control of both the amount of PEG and ALN moieties. Stable DEX-ALN-PEG coatings substantially decreased their internalization by macrophages in vitro, providing new perspectives for biomedical applications.